Decoloniality, interculturality and recognition - Polo Santillán, Miguel Ángel (2017)
The article aims to show that the greatspeeches of great practical theory of our time-decoloniality, interculturality and recognition- are not unrelated proposals, but may be articulated by the decolonial perspective, where the issue of coloniality power can allow to review our ethical concepts and to articulate these practical perspectives.